2008
DOI: 10.1086/589095
|View full text |Cite
|
Sign up to set email alerts
|

β‐Adrenergic Stimulation Enhances the Heat‐Shock Response in Fish

Abstract: We have taken advantage of the unique properties of nucleated rainbow trout (Oncorhynchus mykiss) red blood cells (rbcs) to demonstrate that beta-adrenergic stimulation with the agonist, isoproterenol, significantly enhanced the heat-induced induction of heat-shock proteins (Hsps) in trout rbcs without affecting hsp expression on its own. Furthermore, this beta-adrenergic potentiation of hsp expression occurred only at physiologically relevant concentrations of adrenergic stimulation. In further experiments, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 39 publications
(56 reference statements)
0
11
1
Order By: Relevance
“…4). The lack of catecholamine release contrasts with previous studies on teleosts at elevated temperatures (13,19,56), although the thermal challenges used in these earlier studies were likely more severe. This opens the possibility for venous vasoconstriction mediated by other mechanisms such as nonadrenergic vasoactive agents (15) or myogenic responses as seen in some preparations of mammalian veins (5,14).…”
Section: Acute Warmingcontrasting
confidence: 82%
See 1 more Smart Citation
“…4). The lack of catecholamine release contrasts with previous studies on teleosts at elevated temperatures (13,19,56), although the thermal challenges used in these earlier studies were likely more severe. This opens the possibility for venous vasoconstriction mediated by other mechanisms such as nonadrenergic vasoactive agents (15) or myogenic responses as seen in some preparations of mammalian veins (5,14).…”
Section: Acute Warmingcontrasting
confidence: 82%
“…Furthermore, although numerous studies on both teleosts and elasmobranchs have addressed the effects of hypoxia on catecholamine release, few have studied the effects of acute temperature changes on the humoral catecholaminergic response (13,19,56). Given the apparently sparse adrenergic innervation of the systemic vasculature in the dogfish, we hypothesized that circulating catecholamines might be critical for the control of the capacious venous system of this species.…”
mentioning
confidence: 99%
“…In fishes, Hsp70 genes and protein are dramatically induced with heat shock (Fangue et al 2006;Currie et al 2008;Fowler et al 2009), whereas Hsc70 tends to be weakly induced (Ojima et al 2005) if at all (Zafarullah et al 1992). Thus, our observation that white muscle and liver Hsc70 was significantly induced in both dominant and subordinate fish while Hsp70 was not is somewhat surprising.…”
Section: Discussionmentioning
confidence: 71%
“…Hsp70 is one of the most stress inducible of the Hsps. For example, the inducible isoform of this protein increases approximately 10-fold in recovery from heat shock in rainbow trout tissues (Fowler et al 2009), with gene expression increasing by 300-fold (Currie et al 2008). If social interactions represent a significant cellular stress, we would expect to see clear induction of this Hsp resulting from hierarchy formation and/or prolonged dominant and subordinate interaction.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, independent and interactive effects of exhaustive exercise were clearly apparent. Exhaustive exercise increases epinephrine levels in blood (Opdyke et al, 1982;Butler et al, 1986), and Currie et al (2008) found that the hsp mRNA and protein response to heat stress in red blood cells was similarly exacerbated by epinephrine in rainbow trout Oncorhynchus mykiss (Walbaum 1792). Thus, humoral or neural sympathetic mediation could be involved in the hsp response of the O. nerka ventricle.…”
Section: K a N T T I L A E T A Lmentioning
confidence: 99%